1998
DOI: 10.1007/s004280050282
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of c-met proto-oncogene associated with chromophilic renal cell carcinoma with papillary growth

Abstract: Various genetic changes are involved in human renal cell carcinomas (RCCs). However, the molecular events related to other cytomorphological subtypes of RCC are not well known, apart from the relationship between the von Hippel-Lindau tumour suppressor gene and clear cell subtype RCC. We examined the overexpression of several growth factor receptors immunohistochemically and analyzed their relationship to the cytomorphological characters in 120 cases of RCCs. These receptors included c-met proto-oncogene produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Previous studies demonstrated that the relationship of c-Met expression with tumor differentiation seems to vary among different tumor types [23,37,38]. In the current study, c-Met protein levels were low in well-differentiated colon cancers compared to moderately or poorly differentiated cancers.…”
Section: Discussioncontrasting
confidence: 55%
“…Previous studies demonstrated that the relationship of c-Met expression with tumor differentiation seems to vary among different tumor types [23,37,38]. In the current study, c-Met protein levels were low in well-differentiated colon cancers compared to moderately or poorly differentiated cancers.…”
Section: Discussioncontrasting
confidence: 55%
“…Evaluation of HGFR/c-Met expression was assessed semiquantitatively according to a previous report (16). Briefly, specimens were considered to be positive when >50% of cancer cells showed higher staining than normal kidney.…”
Section: Methodsmentioning
confidence: 99%
“…Activating mutations of HGFR/c-Met have been reported in hereditary type 1 papillary carcinoma (4). Although the same mutation is uncommon in sporadic papillary RCC and is not a typical feature of sporadic conventional RCC, overexpression of HGFR/c-Met is frequently observed (15,16) and it causes ligand-independent activation of receptor tyrosine kinases (17,18). Downstream of overexpressed HGFR/c-Met, phosphoinositide 3-kinase activity is increased (18), which may stimulate proliferation, migration, and survival of renal carcinoma cells through c-Akt and p70 S6 kinase (5,6).…”
mentioning
confidence: 99%
“…4 In renal cell carcinomas, a close correlation was observed between the overexpression of c-met and the chromophilic subtype with a papillary growth pattern. 20 Di Renzo et al 17 found c-met to be most overexpressed in ovarian carcinomas that were differentiated. In the present study, cmet expression was enhanced in most benign tumors and appeared to be maximally overexpressed in differentiated borderline tumors and differentiated ovarian carcinomas.…”
Section: Discussionmentioning
confidence: 99%